We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
345
1
avatar

y = mx + b for b

 Sep 7, 2017
 #1
avatar+7612 
+2

y  =  mx + b

 

To solve this for  b  , let's subtract  mx  from both sides of the equation.

 

y - mx  =  mx + b - mx

 

y - mx  =  b

 

So.......    b  =  y - mx

 Sep 7, 2017

17 Online Users

avatar